Towards Industry Revolution 4.0 Practice: Millennial’s Intention to Use Online Property Websites by Applying the Stimulus-Organism-Response (S-O-R) Model - Chang Mui Ling Dyana; Norazah Mohd Suki; Nelson Lajuni; Rizal Hamid (International Journal of Supply Chain Management, 2019)
Minimal research was explored on consumer behavior towards online property websites in developing countries. Hence, this study aims to inspect factors that affect millennial’s intention to use the online property website by utilizing the Stimulus-Organism-Response (S-O-R) model as the guiding principle. The proposed research framework encompasses 3 aspects of atmospheric cues from the website (ARQW) such as ubiquity (UB), ease of use (EOU) and information exchange (IE) to establish the research hypotheses. PLS-SEM results revealed that the atmospheric cues from web sites (ARQW) such as ubiquity (U), ease of use (EOU) and information exchange (IE) are key determinants of millennial’s intention to use the online property website in Malaysia. This discovery provides important findings on the factors that have strong impact on consumers’ intention regarding online property websites. Suggestions for further research are also provided.